Central adiposity in relation to risk of liver cancer in Chinese adults: A prospective study of 0.5 million people - Pang, Y; Kartsonaki, C; Guo, Y; Chen, Y; Yang, L; Bian, Z; Bragg, F; Millwood, I; Yu, C; Lv, J; Chen, J; Li, L; et al. (Wiley, 2019)
Central adiposity is associated with liver cancer risk beyond general adiposity in Western populations. However, there is little prospective evidence in East Asian populations who are more likely to have central adiposity at given BMI levels. The prospective China Kadoorie Biobank recruited 512,713 adults aged 30–79 years from 10 diverse areas. During 10 years follow‐up, 2,847 incident cases of liver cancer were identified. Cox regression was used to estimate adjusted hazard ratios (HR) for liver cancer associated with central adiposity, excluding individuals with cancers and liver diseases at baseline and the first 5 years of follow‐up (1,049 incident liver cancer cases). Overall, mean waist circumference (WC) was 82.2 (SD 9.8) cm in men and 79.1 (9.5) cm in women. Central adiposity showed positive associations with liver cancer risk. Associations were strongest for WC and waist‐to‐hip ratio (WHR), with adjusted HRs per 1‐SD of 1.09 (95%CI 1.01–1.18) and 1.12 (1.02–1.23), respectively. The positive associations became stronger when additionally adjusting for BMI (1.26 [1.09–1.46] and 1.14 [1.02–1.28]). The positive association of central obesity (WC ≥90 cm in men and ≥ 80 cm in women) with liver cancer increased progressively with the number of other presenting metabolic risk factors (physical inactivity, diabetes, and hypertension), with HRs of 1.07 (0.90–1.28), 1.17 (1.00–1.38), and 1.91 (1.40–2.59) in those with one, two, and three factors (p for trend 0.006). In this relatively lean Chinese population, there were positive associations of central adiposity with risk of liver cancer, with WHR and WC showing the strongest associations.